Hysteresis of the Antarctic Ice Sheet With a Coupled Climate‐Ice‐Sheet Model - G. Leloup; A. Quiquet; D. M. Roche; C. Dumas; D. Paillard (Geophysical Research Letters)
Abstract The stability of the Antarctic ice sheet under different fixed CO2 levels and orbital configurations is explored using a coupled climate‐ice sheet model, starting from either a pre‐industrial ice sheet or an ice‐free, isostatically rebounded geometry. Simulations reveal a strong hysteresis effect: equilibrium ice volumes differ significantly for equivalent CO2 levels, depending on the initial ice sheet geometry. Crucially, the albedo‐melt feedback is accounted for in our coupled setting, resulting in a nonlinear response of the ice sheet to the CO2 forcing. Critical CO2 thresholds trigger either the complete Antarctic ice sheet loss or near‐complete regrowth. The orbital configuration influences these CO2 thresholds. These findings highlight the importance of ice sheet‐atmosphere interactions, notably the albedo‐melt feedback, in projecting future long‐term ice sheet behavior. Neglecting these feedbacks could lead to an overestimation of CO2 thresholds for ice sheet destabilization, with implications for future long‐term sea level rise under high emission scenarios.